2013
DOI: 10.1007/s00262-013-1482-y
|View full text |Cite
|
Sign up to set email alerts
|

Development of a peptide-based vaccine targeting TMPRSS2:ERG fusion-positive prostate cancer

Abstract: Identification of novel vaccine targets is critical for the design and advancement of prostate cancer (PCa) immunotherapy. Ideal targets are proteins that are abundant in prostate tumors while absent in extra-prostatic tissues. The fusion of the androgen-regulated TMPRSS2 gene with the ETS transcription factor ERG occurs in approximately 50% of prostate cancer cases and results in aberrant ERG expression. Because expression of ERG is very low in peripheral tissue, we evaluated the suitability of this protein a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…Another gene that is being targeted 1215 for cancer therapy is ERG transcription factor, the gene 1216 with the most significant copy number gain in our anal-1217 ysis. Several studies have reported their attempts in de-1218 veloping drugs that target the ERG transcription fac-1219 tor, mostly in prostate cancer [244,245]. Further vali-1220 dation of the results described here would suggest the 1221 expansion of such trials to include melanoma.…”
mentioning
confidence: 78%
“…Another gene that is being targeted 1215 for cancer therapy is ERG transcription factor, the gene 1216 with the most significant copy number gain in our anal-1217 ysis. Several studies have reported their attempts in de-1218 veloping drugs that target the ERG transcription fac-1219 tor, mostly in prostate cancer [244,245]. Further vali-1220 dation of the results described here would suggest the 1221 expansion of such trials to include melanoma.…”
mentioning
confidence: 78%
“…In our study, type VI fusions were present in 4 tumors (13%) and in each case led to predicted high-affinity fusion epitopes on autologous HLAs. Indeed, due to the prevalence of ERG alterations in prostate cancer, one study reported vaccine-induced immunity to ERG-derived HLA-A*02:01-restricted epitopes [48]. …”
Section: Discussionmentioning
confidence: 99%
“…Since this discovery, many tumor antigens have been discovered that could be targeted by vaccines [15][16][17]. Based on these discoveries, several approaches using traditional antigen delivered in various adjuvants have been used to expand a population of tumor antigen specific T-cells.…”
Section: Using Vaccines To Treat Cancermentioning
confidence: 99%